Couples en emploi et morphologie sociale des quartiers de Montréal, 1971-1991 - Villeneuve, Paul (Sociologie et sociétés, 1995)
issued: 1995-23-00
Keywords: Femmes; Quartiers; Travail

Asymétrie occupationnelle et localisation résidentielle des familles à double revenu à Montréal - Villeneuve, Paul; Viaud, Gilles (Recherches sociographiques, 1987)
Number: 2-3
Keywords: Famille

Mesurer la diversité et les inégalités dans les villes canadiennes - Villeneuve, Paul (La métropolisation et ses territoires, 2009)
Keywords: Pauvreté

Les flux de transport par autobus entre Montréal et sa région - Villeneuve, Paul; Delphanque, France; Roy, Jacques (Revue de Géographie de Montréal, 1974)
Number: 3
Keywords: Autobus; Transport en commun

Attracting Foreign Students: The Case of Two Universities in Québec - Racine, Nicolas; Villeneuve, Paul Y.; Thériault, Marius (Journal of Studies in International Education, 2003)
A number of factors may influence the recruitment of foreign students by universities, especially economic criteria pertaining to profitability. This article examines the cases of two Québec universities. Both feature teaching exclusively in French, a minority language in North America. Based on existing literature, hypotheses concerning the impact of language and international networking on the recruitment of foreign students are tested. Analysis reveals that even if regular use of French is important for recruitment, it is not the only variable involved. The geographical and social context of each university also plays an important role, as does the networking activities of academics who build relationships based on cooperation with foreign institutions.
Number: 3
Keywords: Université de Montréal; Étudiants

Double emploi et rang social des quartiers de Montréal - Villeneuve, Paul; Morency, René (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Quartiers; Travail

Power and Decision-Making in the City: Political Perspectives - Villeneuve, Paul; Séguin, Anne-Marie; Bunting, Trudy E.; Filion, Pierre (Canadian Cities in Transition: The Twenty-First Century, 2000)